Educational Management: Cultural-Based Islamic School Branding Strategies in Building Public Trust at Amaliah Elementary School, Ciawi - Kari, Fendra; Muhtadin; Herlina, Lina (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze the branding strategy of Islamic schools based on school culture in building public trust at Amaliah Ciawi Elementary School. The study used a qualitative approach with a phenomenological type to understand the experiences and perceptions of informants regarding the branding practices carried out. Data were collected through in-depth interviews, participant observation, and documentation studies, with informants consisting of the principal, teachers, and parents. Data analysis used the interactive model of Miles, Huberman, and Saldana which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the school culture based on the value of tauhid is the main foundation in building authentic branding. The branding strategy is implemented through an inside-out approach , where the school image is built from the consistency of internal practices such as religious habits, character learning, and teacher role models. Teachers act as brand ambassadors who directly influence public perception through professional and Islamic-valued interactions. Public trust is formed from the conformity between the communicated values and the actual experiences felt, which is reflected in the increasing number of enrollees, parental satisfaction, and loyalty based on word of mouth . This study concludes that effective Islamic school branding does not depend solely on external promotion, but rather on the strength of the school culture, consistently internalized in educational practices. Therefore, strengthening organizational culture and the quality of human resources is key to building sustainable public trust